A Preliminary Studies of Fish Richness in the Tondano River Estuary Manado Bay - Bataragoa, Nego E.; Pratasik, Silvester Benny; Menajang, Febry S. I.; Manginsela, Fransine B.; Dauhan, Dulce Maria; Tombi, Indra (Jurnal Ilmiah Platax, 2023)
The purpose of this study was to analyze the richness of fish species in the Tondano River estuary. Sampling was done for two months, in July and August 2022, new moon phase, during the low tide at 13.00-16.00 pm. Sampling used a 20-m beach seine with a cod-end part of 0.2-cm mesh and wings of 2-m height and 1.5-cm mesh. The beach seine was operated 10 times starting from the lowest tide at 13.00 pm to the tide condition at 16.00 pm. As a whole, 736 individuals were caught, consisting of 24 species and 17 families, 14 migrant species, and 10 resident species The number of fish varied from 1 to 445 individuals, in which Terapon jarbua (445 ind) was the most abundant, followed by Neovespicula depressifrons (70 ind). The dominant index (C) was 0.38 and the diversity index (H) was 1.65. The resident species were 120 individuals varying from 2 to 70 ind., and the most abundant was Neovespicula depressifrons (70 ind.). The dominant index (C) was 0.37 and the diversity index was 1.47.